The Quality of Health Services in Tawaeli Health Center, Tawaeli District, Palu City - Dian Angraeni; H. Abu Tjaiyya; Muhammad Akhyar; Abd. Muhaimin Tayeb (Universitas Negeri Makassar, 2018)
Effective public services carried out by governments or corporations can strengthen democracy and human rights, promote economic prosperity, reduce poverty, improve environmental protection, be wise in the use of natural resources, deepen trust in government and public administration. The purpose of this study was to determine how the quality of health services at the Tawaeli Health Center, Tawaeli District, North Palu. This type of research is qualitative research that is a study used to investigate, describe and explain a phenomenon or problem. To find out the quality of health services in the Tawaeli Health Center according to Zeithaml-Parasuraman-Berry there are four indicators used namely tangible, reliability, responsiveness, assurance, and empathy. There are 8 informants in this study with accidental technique, which is the technique of determining samples based on chance. The results in this study indicate that the Health Services at the Tawaeli Health Center in the District of Tawaeli in Palu City are seen from several aspects that are still not good, the first is tangible, responsiveness is also still lacking. However, seen from the aspects of reliability, assurance, and empathy, it was considered good.